Races of Sphaerotheca fuliginea infecting cucurbits in India and host differentials for their identification - G.K. SHARMA, M. WAJID KHAN and (Indian Phytopathology, 2002)
Analysis of a large number of isolates of Sphaerotheca fuliginea collected from different cucurbits showed occurrence of three races in most of the agro-ecological zones of India. Race 3 was most widespread and infected most of the cultivated cucurbits in the states. Race 2 was restricted to green melon, Citrullus vulgaris var. fistulosus and race 1 to spongegourd, Luffa cylindrica. In addition, race 1 infected a few other cucurbits. L. cylindrica, C. vulgaris var. fistulosus and Cucumis sativus are proposed as differential hosts for identification of the three races of S. fuliginea isolated from cucurbits.